Pengaruh Gaya Hidup Dan Motivasi Belajar Mahasiswa Pendidikan Matematika - Aisyah, Adinda (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
The objective of this research is to determine whether lifestyle significantly affects learning motivation. This study employed a quantitative approach with an ex post facto design, involving 54 randomly selected respondents. Data were collected using questionnaires distributed via Google Form and analyzed using simple linear regression and ANOVA tests. The results showed no significant effect of lifestyle on students’ learning motivation. Although the relationship direction appeared negative, the influence was very weak and statistically insignificant. These findings indicate that lifestyle is not a major factor in shaping students’ learning motivation. Future research is recommended to explore other variables such as academic goals, learning interest, and social support as more relevant predictors of learning motivation